Proximate analysis and fatty acid profile of lablab (Benthic mat). - Madas, Jeanette B. (2002.)
Lablab (benthic mat), as locally known in the panay Region of the Philippines is a complex of both micro and macroscopic organisms, which settles on, above, or within substrates of seas, rivers, ponds, and lakes. Some local fish farmers have been utilizing these complexes as natural food for their cultured fishes. Lablab from Brgy. nabitasan, leganes, Iloilo was proximately characterized and analyzed for its fatty acid profile in order to asses its potential as food for cultured species, as well as a source of polyunsaturated fatty acids., The proximate characterization showed that air-dried lablab contained low moisture content (7.7 percent), high level of minerals (79.05 percent), moderate amounts of ether-soluble substances (6.11 percent) and protein (5.28 percent), and a very low fiber (0.12 percent). Moreover, the fatty acid profile, determined using a gas chromatogram, revealed that lablab was a good source of both saturated and unsaturated fatty acids. Palmitic acid being the most abundant, constituted 32.1 percent of the fatty acid mixture, followed by oleic acid (13.1 percent) and an unidentified component E (13.0 percent). Moderate amounts of component F (8.2 percent), component A (7.8 percent), linoleic acid (4.8 percent), and myristic acid (4.8 percent) were also present. Only nine fatty acids were identified due to the unavailability of appropriate standards. The results of these analyses showed that the lablab had high nutritional value and could be a potent source of essential fatty acids.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Lablab; Benthic mat